Prevalence of depression among health sciences students: Findings from a public university in Malaysia - Fata Nahas, Abdul Rahman; Elkalmi, Ramadan Mohamed Mahmod; Mohammed Ahmed, Abdul Kareem; Elsayed, Tarek Mohamed Ali (Medknow Publications and Media Pvt. Ltd, 2019)
Background: High rates of psychological problems including depression among university students have been reported in various studies around the world. The objectives of this study were to explore the prevalence of depressive disorder, as well as the associated sociodemographic factors (gender, origin, school, and year of study) among health sciences students. Materials and Methods: This cross-sectional study was conducted among 425 students from 5 different schools of health sciences at International Islamic University Malaysia, using the Patient Health Questionaire-9 (PHQ-9). Results: With a response rate of 85.9% (n = 365), the results showed a depressive disorder prevalence of 36.4%. The mean PHQ-9 score of the respondents was 8.10 (SD = 4.9), indicating mild depression severity. A statistically significant association was revealed between gender and severity of depression (P = 0.03), as well as between students’ origin and severity of depression (P = 0.02). Conclusion: The findings indicated high prevalence of depression among undergraduate health sciences students. While providing significant information to students’ affairs department, the study findings suggest the necessity to address depressive disorder in health sciences university students in Malaysia. Future research is needed to confirm these results in larger samples.